2019
DOI: 10.1038/s41598-019-51582-2
|View full text |Cite
|
Sign up to set email alerts
|

Habitat availability explains variation in climate-driven range shifts across multiple taxonomic groups

Abstract: Range shifting is vital for species persistence, but there is little consensus on why individual species vary so greatly in the rates at which their ranges have shifted in response to recent climate warming. Here, using 40 years of distribution data for 291 species from 13 invertebrate taxa in Britain, we show that interactions between habitat availability and exposure to climate change at the range margins explain up to half of the variation in rates of range shift. Habitat generalists expanded faster than mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 40 publications
7
115
0
Order By: Relevance
“…UKCEH Biological Records Centre data), specifically examining changes in landscape occupancy and rates of range expansion in relation to local set‐aside availability. Our range expansion results do align with empirical assessments of distributional shifts within the UK which highlight the importance of additional habitat at the leading edge of expansions for a diverse range of taxa including grassland flying insects (Platts et al ), and that for certain species, small amounts of extra habitat can have big effects on range expansion (Hill et al ).National AES programs are expensive and environmental subsidies should be carefully designed to make best use of public funds. In testing how well the existing distribution of set‐aside strips fares against alternative strategies of spatial distribution, we found that altering the aggregation or area of set‐aside strips could substantially improve range expansion, but there was no clear consensus on which strategy was universally better.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…UKCEH Biological Records Centre data), specifically examining changes in landscape occupancy and rates of range expansion in relation to local set‐aside availability. Our range expansion results do align with empirical assessments of distributional shifts within the UK which highlight the importance of additional habitat at the leading edge of expansions for a diverse range of taxa including grassland flying insects (Platts et al ), and that for certain species, small amounts of extra habitat can have big effects on range expansion (Hill et al ).National AES programs are expensive and environmental subsidies should be carefully designed to make best use of public funds. In testing how well the existing distribution of set‐aside strips fares against alternative strategies of spatial distribution, we found that altering the aggregation or area of set‐aside strips could substantially improve range expansion, but there was no clear consensus on which strategy was universally better.…”
Section: Discussionsupporting
confidence: 83%
“…Range shifts in response to climate change are well documented (Walther et al , Chen et al ) and habitat availability has been shown to be a key factor influencing rates of range shifting (Hill et al 1999, Platts et al ). Integrating stepping‐stone habitat within landscapes has been identified as an effective way of facilitating range shifts (Hodgson et al , Saura et al , Hannah et al ) and our study shows that agri‐environment options such as set‐aside field margin strips can serve this stepping‐stone function for dispersal‐limited species.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge for researchers with long-term data is to develop statistical models that encompass interactions rather than focusing only on main effects that might be easier to interpret. A notable example of modeling interactions in the context of global change comes from a recent study of British insects, where researchers found that the most successful model for poleward range shifts included habitat availability, exposure to climate change, and the interaction between the two (25).…”
Section: On the Relative Importance Of Climate Change And Other Stresmentioning
confidence: 99%
“…As a result, climate warming may cause a spatial mismatch between suitable climatic conditions and habitat availability [19][20][21] . Under these circumstances, habitat distribution and quality are expected to play a central role in explaining local population dynamics and climate-induced range shifts [22][23][24][25][26] , in particular for specialist, rare and threatened species whose range shift dynamics are likely to be most sensitive to the elevational distribution of suitable habitats.…”
mentioning
confidence: 99%